Herbicide strategies for weed control in Wisconsin conventional-tillage corn production systems - Ahmadreza Mobli; Ryan P. DeWerff; Nicholas J. Arneson; Daniel H. Smith; Rodrigo Werle (Weed Technology)
Selection of effective herbicide strategies (i.e., one-pass versus two-pass and timing [preemergence versus postemergence]) is of great importance to corn growers. Field studies were conducted to evaluate overall end-of-season weed control efficacy of multiple herbicide strategies in conventional tillage corn production systems. These studies were carried out over six site-years at four locations in Wisconsin: Arlington (2018 and 2019), Brooklyn (2019), Lancaster (2019), and Janesville (2018 and 2019). Herbicide strategy treatments included one-pass preemergence, one-pass postemergence, two-pass preemergence followed by (fb) postemergence, and two-pass preemergence fb postemergence with layered residual herbicides. The weed species present at the experimental site-years included common lambsquarters, giant foxtail, giant ragweed, velvetleaf, and waterhemp. Except Arlington-2019, the herbicide strategy was not as influential for the site-years infested with common lambsquarters, giant foxtail, velvetleaf, and waterhemp species (e.g., Arlington-2018, Brooklyn-2019, Lancaster-2019), as effective overall end-of-season control (>90%) was achieved regardless of the herbicide strategy, and no significant differences were observed in the combined weed biomass across strategies. A two-pass strategy (e.g., preemergence followed by postemergence, or preemergence followed by postemergence with layered residual herbicides) was necessary for effective overall end-of-season control at the site-years infested with giant ragweed (Janesville-2018 and -2019). Weed interference reduced corn yield by 11% to 75% across site-years. Although certain weed communities can be effectively controlled by a one-pass herbicide strategy, two-pass strategies provided the greatest and most consistent overall end-of-season weed control and corn yield across all site-years, regardless of weed species composition and environmental conditions. Hence, a two-pass herbicide strategy is recommended for conventional-tillage corn production in Wisconsin to ensure effective end-of-season weed control while protecting yield potential of the crop, particularly in fields infested with moderate to high density of troublesome weeds such as giant ragweed.